Experimental Investigation of Tritium Compatible Stainless Steel Roots Pumps: Part 1: Evaluation of light gas pumping performance and integrity of the shaft mechanical seal. (5th June 2022) - Banerjee, Indranil; Schopphoff, Andreas; Hughes, Shaun; Pearce, Robert; Nasluzov, Sergei
Summary: The tritium compatible Roots pump Okta 1500 (Pfeiffer Vacuum) is designed for pumping light gas species consisting of diluted radioactive gas, especially tritium mixed with other hydrogen isotopes and helium. Therefore, the pump is constructed of stainless steel and equipped with a special gas lubricated mechanical seal. The series of experiments presented in this work include the evaluation of the performance and an integrity check of the glide ring seal as well as the determination of the light gas pumping performance at low pressure. Those qualifications are needed for efficient embedding of the pump in the International Thermonuclear Experimental Fusion Reactor (ITER) project. As a nuclear facility (Installation Nucléaire de Base, INB) ITER is operated in accordance with the French nuclear safety regulations (INB guidelines) that demand qualification and integrity of the tritium bearing equipment to maintain performance and confinement of active gases at every stages via design, testing, commissioning, operation and surveillance. The experimental methodologies and findings are important to advocate the qualification of the pump for the purpose of radioactive light gas pumping as a roughing pump to back Torus high vacuum cryogenic pump. Zusammenfassung: Experimentelle Untersuchung tritiumtauglicher Edelstahl‐Wälzkolbenpumpen – Bewertung der Pumpleistung für leichte Gase und der Integrität der Gleitringdichtung Die tritiumtaugliche Wälzkolbenpumpe Okta 1500 (Pfeiffer Vacuum) ist speziell für das Fördern von leichten Gasen ausgelegt, welche im Fall des Internationalen Thermonuklearen Experimentell Reaktors ITER aus verdünntem radioaktivem Tritium sowie anderen Wasserstoffisotopen und Helium bestehen. Um den Anforderungen im Betrieb zu genügen, ist die Pumpe komplett in Edelstahl ausgeführt und mit einer speziellen gasgeschmierten Gleitringdichtung ausgestattet. Die hier vorgestellten Experimente umfassen die Bewertung der Leistung und Integritätsprüfung der Gleitringdichtung sowie die Bestimmung des Saugvermögens für Gase bei niedrigem Druck. Diese Qualifikationen werden für eine effiziente Einbindung der Pumpe in ITER benötigt. Als Nuklearanlage (Installation Nucléaire de Base, INB) wird ITER in Übereinstimmung mit den französischen Vorschriften zur nuklearen Sicherheit (INB‐Richtlinien) betrieben, die die Qualifikation und Integrität der tritiumführenden Komponenten sicherstellen sollen. Die Richtlinien sehen in allen Phasen, nämlich Entwurf, Prüfung, Inbetriebnahme, Betrieb und Überwachung, die Kapselung aktiver Gase vor. Die hier vorgestellten Ergebnisse ermöglichen die Qualifizierung der Pumpe für die Verwendung als Grobvakuumpumpe für leichte, radioaktive Gase zur Unterstützung der Torus‐Hochvakuumkryogenpumpe zu ermöglichen.